Закономірності поширення флуктуації гірського тиску у виробленому просторі діючої лави - Назимко, В.В.; Назимко, І.В. (Физико-технические проблемы горного производства, 2016)
Досліджено процес поширення флуктуації гірського тиску у виробленому просторі діючого очисного вибою. Встановлено залежність величини затримки прояву флуктуації у вигляді збурення напружено-деформованого стану масиву від її амплітуди та розподілу. Исследовано процесс распространения флуктуации горного давления в выработанном пространстве действующего очистного забоя. Установлено зависимость величины задержки макроскопических последствий флуктуации от амплитуды флуктуации и ее распределения. We simulated a ground pressure fluctuation as 5 adjacent powered supports failure during a day. The main roof has been presented as a plate that lies on the rigid base. Stiffness of the base depends on thickness of extracted coal seam and dilation of caving roof. Maximum stiffness occurs in situ, minimum - in the gob when the roof is highly flexible and subsides elastically, without caving. The more stress in the roof the higher cavity occurs and the larger increment of the base stiffness. The wave of the fluctuation has extended both to the direction of the longwall advance and along the face from the point of the fluctuation stimulation. There was an incubation period when effect of the fluctuation was negligible and process of main roof caving kept unaffected. Distance of the longwall advance during incubation period was twice as the longwall length for the fluctuation magnitude of 1% relatively maximum disturbance and 0,2 of the longwall length for the magnitude of 24%. However the pattern of the roof caving has dramatically changed during farther movement of the longwall. All caving parameters have changed: step of the caving, ground pressure distribution and its manifestation in the longwall and its entries. Histogram of the fluctuation magnitude was symmetric and in accordance with normal distribution having a big excess. These findings are the first step to answer the question: whether it possible to forecast process of main roof caving and weighting consistently.